Transcranial Doppler Can Predict Development and Outcome of Sepsis-Associated Encephalopathy in Pediatrics With Severe Sepsis or Septic Shock - Algebaly, HebatAllah; ElSherbini, Seham; Galal, Ahmed; Hamdi, Rania; Baz, Ahmed; Elbeleidy, Ahmed (Frontiers in Pediatrics, 2020)
Background and Aim: Sepsis is a common cause of pediatric intensive care unit (ICU) admission. Sepsis-associated encephalopathy (SAE) may occur owing to brain dysfunction in those patients and may be related to impaired cerebral microcirculation. Transcranial Doppler (TCD) can be used to detect this impairment. In this study, we aimed to assess the role of TCD in prediction of SAE and mortality in patients with severe sepsis or septic shock admitted to PICU. Patients and Methods: This prospective study included 75 children admitted to PICU owing to severe sepsis or septic shock. Upon admission, all patients were subjected to careful history taking, thorough clinical examination, and standard laboratory workup. Severity of clinical illness was assessed using the Pediatric Risk of Mortality (PRISM) III score. TCD was performed on the first day of admission after the normalization of systolic blood pressure with or without vasopressors. The primary study outcome was differences in the measurement of TCD in SAE, and the secondary outcome was discharge from ICU or mortality. Results: The study comprised 45 children with SAE and 30 age- and sex-matched children without SAE. In this study, SAE patients had significantly higher pulsatility index [PI; median interquartile range (IQR): 1.15 (0.98–1.48) vs. 1.0 (0.95–1.06), p = 0.002] and resistive index [RI; median (IQR): 0.68 (0.61–0.77) vs. 0.62 (0.59–0.64), p = 0.001] than had non-SAE patients. PI and RI showed good performance as predictors of subsequent SAE development [area under the curve (AUC): 0.72 and 0.73, respectively]. Non-survivors in SAE patients had significantly higher PRISM III. Receiver operating characteristic (ROC) curve analysis showed good performance of PI and RI as predictors of mortality at the end of follow-up. Conclusions: In children with SAE, cerebrovascular resistance is high and is associated with increased mortality.